Clima laboral en el Centro De Salud de la Parroquia Barreiro - García Paredes, Mavie De La Cruz (2019)
The work environment of the institutions is fundamental for the achievement of internal objectives, for this reason, it is considered as an indicator of organizational development management; In the Health Center, the attention to the user is conditioned by the inadequate development of activities, because through the investigative methodology constituted by the inductive method, descriptive research, the interview technique and the questionnaire, the existence was determined of inappropriate behaviors and behaviors by health professionals, such as personalities clash, unpunctuality and inappropriate appointment scheduling, there is also a weak document management, which causes the delay of internal processes that affect the supply of quality medical services